Growth, infection and aggressiveness of Phytophthora pathogens on Rhododendron leaves - Clare R. Taylor; Niklaus J. Grünwald (CABI Agriculture and Bioscience)
Abstract Background Phytophthora species are well known as important or emerging pathogens. The genus Rhododendron is of considerable importance to plant regulatory agencies because it is host to many Phytophthora species, most notably, P. ramorum and P. kernoviae. Few studies have directly contrasted the epidemiology of different Phytophthora spp. on a given host. Methods We investigated aspects of the foliar epidemiology (lesion size, sporulation and temperature responses) of P. cactorum, P. cambivora, P. cinnamomi, P. citrophthora, P. foliorum, P. kernoviae, P. lateralis, P. nemorosa, P. nicotianae, P. plurivora, P. ramorum and P. syringae on Rhododendron in detached leaf, whole plant chamber, and field studies. Results P. syringae stood out as it appeared to be a relatively weak pathogen, showing no sporulation and low levels of disease severity, except at low temperatures. P. nicotianae was consistently able to grow at higher temperatures than any of the other Phytophthora spp. and showed higher aggressiveness than any of the other species at high temperatures. P. cinnamomi and P. cactorum, typically thought of as root-infecting species, were able to cause as much foliar disease as P. syringae, a foliar pathogen. P. kernoviae was consistently among the most aggressive species with the highest sporulation. Conclusion These results provide novel insights into the comparative epidemiology of these important established and emerging Phytophthora species.